If f(X,Y)=g(X,Y-1)+1, g(X,Y)=f(X-1,Y)+1, f(X,0)=0, g(0,Y)=0, find f(X,Y)

Did you figure out first : g(x, y-1) = ?

No, I was thinking like as
f(x,0)= 0, here y=0. So it is equal to g(x,-1)+1.
g(0,y)=0, here x=0. So it is equal to f(-1,y)+1.

But I have no idea what I can say about f(x,y) unless both are zeros.


 
No, I was thinking like as
f(x,0)= 0, here y=0. So it is equal to g(x,-1)+1.
g(0,y)=0, here x=0. So it is equal to f(-1,y)+1....
What happened when you tried following the helper's hint? ;)
 
Top